أسلوب الترغيب والترهيب عند الداعية د ا رسة تحليلية لخطب الشيخ البشير الإب ا رهيمي - هزلة, رفيدة; عباد, آمنة; زبيدي, فاطمة الز هراء (جامعة الوادي university of eloued, 2017)
يهددف ىدذا البحدث إلى البَكيدز بلدى أسدلوب البَبيدب والبَىيدب بُ خطدب بؿمدد البشدبّ الإبراىيمدي كأبموذجدا الدذي يعدد أحدد خطبداء ابعزائدر ومدذلك أحدد رواد ابغركدة الإصدلبحية بُ ابعزائر وذلك كانت دراستنا برليلية دقيقة بالنسبة إلى الأسلوبي البَبيب والبَىيب الدبٍ ألقاىدا بُ مناسدبات متعدددة سدعى فيهدا إلى صدلح النداس وإرشدادىم بكدو الطريدق القدو مدن خدلبل أسدلوب البَبيب والبَىيب والدفاع عن ابؼقومدات الأمدة ابعزائريدة إلى أراد ابؼسدتدم ممدلم معابؼهدا والقضداء عليها بضرب عقيدتها ودينها ولغتها. Abstract The aim of this research is the focus on the style of intimidation and the style of motivation in the speechs of Mohammed Albachir Alebrahimi ; who is considered one of the official Algerian speakers and one of the piooners of the reformist movements in algeria ; our study was accurate and analytical conserning those styles . Which he presented in various ocations and events persuing the peace of people and to guide them to the right path throught the styles of motivation and intimidation and the protection of the algerian nation's values which the invaders wanted to erase and distroy by targeting it's belifs , it's religion and it's language